Transformational Leadership and Performance: Testing Mediation and Moderation in Qatari Hospitality Industry - Al-Khulaifi , Dr.Ebrahim; Younus, Muhammad Kashif (Archives of Business Research, 2021)
This study aimed to determine organisational performance with the perspective of employees' service performance by leadership in the hospitality industry. For doing so, we hypothesised the relationship of transformational leadership and employees' service performance via two roots, service climate and organisational identification. Furthermore, to examine the leadership role in service climate development and organisational identification, we used proactive personality as the boundary condition to these relationships. Data for the study was collected from a diverse range of organisations operating in the Qatari hospitality industry. Findings showed that the service climate fully mediates the relationship, while organisational identification failed to mediate the relationship. Considering the moderating effects, results suggested that strong proactive personalities will strengthen transformational leadership on service climate and organisational identification. This study als0 discussed various theoretical and managerial implications.